New evidence on prognostic features, prevention and treatment of congenital Cytomegalovirus infection. Issue 5 (October 2020) - Sebghati, Mercede; Khalil, Asma
Abstract : Purpose of review: Congenital Cytomegalovirus (CMV) infection remains a major cause of lifelong disability, with no systematic screening implemented in pregnancy or the postnatal period. In this review article, we outline the preventive strategies, antenatal prognostic features and experimental therapies as well as evidence of efficacy from recent trials. Recent findings: A recent randomized, double blinded, placebo-controlled study investigated the efficacy of Valaciclovir in women contracting primary CMV in the periconception period or first trimester. They concluded that Valaciclovir at a dose of 8 g/day is effective in reducing the rate of foetal CMV infection following early maternal primary infection. Administration of CMV hyperimmune globulin (HIG) was investigated in a recent randomized double-masked controlled trial. This study concluded that CMV HIG was ineffective at reducing the risk of congenital CMV among women with primary CMV in early pregnancy. Summary: Congenital CMV infection remains a significant cause of disability. There is currently no vaccine available, with the best preventive strategy being patient education on transmission as well as hygiene measures to reduce risk of exposure. Experimental therapies have been investigated in recent years and there is evidence supporting the use of Valaciclovir. Data for the efficacy of CMV HIG remains inconsistent and administration is currently limited to clinical trial settings.